Effect of Copper Alloying and Reinforcement Percentage on the Microstructure-Tribological Aspects of the Aluminium Alloy Composites. (2018) - Ashwath, P.; Jeyapandiarajan, P.; Xavior, M. Anthony; Somani, Mayank; Dharnia, Utkarsh; Grover, Himanshu
Abstract: In this study, microstructural and tribological analysis of Aluminium Alloy composites 2024 and 2900 is done. The composite with reinforcements SiC and Al2 O3 from 0-20 wt% is prepared by powder metallurgy process. As microwave sintering is the process used the core is much denser than at the surface. Strength of aluminium is increased by percentage of copper alloyed in aluminium matrix. Microstructure of the sample is examined thoroughly using scanning electron microscope. X-ray diffraction patterns are investigated for the elements present in the composites and a detailed check for the intermetallic precipitates and the impurities. A uniform microstructure is obtained by microwave sintering process. Aluminium alloy 2024 and 2900 which is microwave sintered is having round-edged porosities with high ductility and toughness. Tribological studies are carried out using pin on disc wear testing machine. The results indicated that 2900 exhibited excellent frictional coefficient behavior compared to AA 2024.